"I see absolutely nothing wrong with that in fact I think …": Functions of modifiers in shaping dynamic relationships in dissertation defenses. Issue 28 (July 2017) - Lin, Chia-Yen
Abstract: This study examines the distribution and cumulative effects resulting from the interplay of diverse salient modifiers in question-response sessions in dissertation defenses. The quantitative results of the study show a high prevalence of modifiers used in the defense corpus. These results are consistent with findings observed in other native and non-native corpora of various academic spoken genres, confirming their crucial importance across generic, cultural and disciplinary boundaries. Statistical comparison of modifiers between the committee and candidate sub-corpora reveals a high degree of homogeneity in type and frequency, except for certain modifiers prefacing disagreement, involvement and intrusion of a subjective stance. Significant numerical discrepancies can be attributed to committees' institutional obligations to question, challenge candidates by introducing conflicting opinions and evoke common ground in the consensus-seeking process. However, qualitative analysis of the majority of common modifiers reveals that their genre-bound functions are largely shared by the opposing groups as strategic elements for securing their original contributions to disciplinary knowledge in the rhetorical encounter. These modifiers contribute to the construction of dynamic relationships between participating academics via their distinctive patterns in the dynamics of interaction. Highlights: The study examines the frequency and functions of modifiers in oral defenses. High statistical homogeneity is demonstrated between committees and candidates. Interpersonal and textual functions of modifiers are largely shared. Dynamic relationships are forged in various interactional patterns. Stances, rhetorical strategies and communicative aims are contributing factors.